2017
DOI: 10.1111/1541-4337.12320
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary Phenolic Compounds in Protein Digestion and Processing Technologies to Improve Their Antinutritive Properties

Abstract: Digestion is the key step for delivering nutrients and bioactive substances to the body. The way different food components interact with each other and with digestive enzymes can modify the digestion process and affect human health. Understanding how food components interact during digestion is essential for the rational design of functional food products. Plant polyphenols have gained much attention for the bioactive roles they play in the human body. However, their strong beneficial effects on human health h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(103 citation statements)
references
References 141 publications
0
100
1
2
Order By: Relevance
“…Under high polyphenolic intake, most polyphenols remain in the gastrointestinal tract because of the low absorption rate of phenolic compounds in the intestine. In this organ, these polyphenols produce inhibitory effects on enzymes involved in the degradation of nutrients, such as α-amylase, saccharides, lipases, and proteases (Cirkovic-Velickovic & Stanic-Vucinic, 2017;Marques et al, 2016), thus reducing nutrient digestibility (Adamidou et al, 2009). In this sense, a decrease in dry matter digestibility was recorded in the second experiment in treatments with higher phenolic content (D12 and D18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high polyphenolic intake, most polyphenols remain in the gastrointestinal tract because of the low absorption rate of phenolic compounds in the intestine. In this organ, these polyphenols produce inhibitory effects on enzymes involved in the degradation of nutrients, such as α-amylase, saccharides, lipases, and proteases (Cirkovic-Velickovic & Stanic-Vucinic, 2017;Marques et al, 2016), thus reducing nutrient digestibility (Adamidou et al, 2009). In this sense, a decrease in dry matter digestibility was recorded in the second experiment in treatments with higher phenolic content (D12 and D18).…”
Section: Resultsmentioning
confidence: 99%
“…Grape pomace (GP) is made from solid residues produced after the juice is extracted from grapes (around 20% of total), consisting of seeds, skin, and stems used in ethanol production by fermentation (Trošt et al, 2016). GP contains antinutritional factors (such as phenolic compounds) (Brenes, Viveros, Chamorro, & Arija, 2016), widely known as digestive enzyme inhibitors (Cirkovic-Velickovic & Stanic-Vucinic, 2017;Førde-Skjaervik, Refstie, Aslakse, & Skrede, 2006). In addition, it is of low nutritional value (protein ≤10%, lipids ≤12%, and carbohydrates 33-50% as fiber), which varies according to grape type and proportion of seeds, skin, and stems (Guerra-Rivas, Gallardo, Mantecón, del Alamo-Sanza, & Manso, 2016;Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic nuclei and hydroxyl group of the aromatic ring of the phenolic compounds provide the principal binding sites for protein‐phenolic complexation . It has been suggested that hydrogen bonding between the phenolic hydroxyl group and the NH‐ and CO‐groups of proteins are involved in protein–phenolics interaction . These interactions result in formation of insoluble complexes which ultimately reduces the digestibility of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols decrease protein digestion in vitro due to their covalent, as well as noncovalent interactions with proteins. Regarding the influence of phenolic compounds on the digestibility of other nutrients, after food intake, most of the consumed polyphenols remain in the GIT, where they can then exert inhibitory effects on enzymes involved in the degradation of saccharides, lipids and proteins (Cirkovic Velickovic & Stanic‐Vucinic, ). Polyphenol compounds have been shown to inhibit crucial enzymes involved in the digestion of starch and lipid (Boath et al ., ; Sakulnarmrat et al ., ; Lochocka et al ., ), as well as protein (He et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol compounds have been shown to inhibit crucial enzymes involved in the digestion of starch and lipid (Boath et al ., ; Sakulnarmrat et al ., ; Lochocka et al ., ), as well as protein (He et al ., ). The effects of phenolic compounds on protein digestibility are consequences of their binding to endogenous proteins, mainly digestive proteases (inhibition, activation, none), as well as protein substrates, which further influences protease activity and protein substrate accessibility (Cirkovic Velickovic & Stanic‐Vucinic, ). Therefore, the reactions of enzymes and protein substrates with phenolic compounds can be influenced by their AA sequence/profile, molecular size and structure.…”
Section: Resultsmentioning
confidence: 99%